Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2174/156720212799297100
|View full text |Cite
|
Sign up to set email alerts
|

PDGF Receptor β Signaling in Pericytes Following Ischemic Brain Injury

Abstract: Platelet derived growth factor (PDGF)-B plays a neuroprotective role in brain damages, including ischemic stroke. It has been suggested recently that PDGF receptor β (PDGFRβ) expressed in brain pericytes as well as in neurons and astrocytes may mediate the neuroprotective role of PDGF-B. The aims of this study were to elucidate the roles of PDGFRβ signaling in brain pericytes after ischemic stroke. In a rat middle cerebral artery occlusion (MCAO) model, PDGFRβ expression was induced specifically in the pericyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 28 publications
5
118
0
Order By: Relevance
“…We and others have reported that PDGFRβ-positive pericytes produce various trophic factors, such as bFGF (basic fibroblast growth factor), NGF (nerve growth factor), BDNF (brain-derived neurotrophic factor), and NT-3 (neurotrophin-3), that are involved in astrocyte survival and activation. 14,26,37 The experiments using PDGFRβ +/-mice support the concept that intrainfarct fibrosis may enhance peri-infarct astrogliosis ( Figure 5). …”
Section: Roles Of Cd34-positive Endothelial Cells and Pdgfrβ-positivesupporting
confidence: 59%
See 2 more Smart Citations
“…We and others have reported that PDGFRβ-positive pericytes produce various trophic factors, such as bFGF (basic fibroblast growth factor), NGF (nerve growth factor), BDNF (brain-derived neurotrophic factor), and NT-3 (neurotrophin-3), that are involved in astrocyte survival and activation. 14,26,37 The experiments using PDGFRβ +/-mice support the concept that intrainfarct fibrosis may enhance peri-infarct astrogliosis ( Figure 5). …”
Section: Roles Of Cd34-positive Endothelial Cells and Pdgfrβ-positivesupporting
confidence: 59%
“…Immunohistochemistry and immunofluorescence were performed as described previously 26 and in Methods in the online-only Data Supplement. microtubule-associated protein 2 (MAP2), GFAP-, CD34-, platelet-derived growth factor receptor β (PDGFRβ)-, and F4/80-positive areas and infarct volumes were quantified using ImageJ software in a blinded manner as described in Methods in the online-only Data Supplement.…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Fibrous tissues may prevent normal tissue recovery, particularly in the muscle where fibrosis has been shown to lead to progressive skeletal muscle injury, for example in Duchenne's muscular dystrophy (Acuna et al, 2014). Previous work has suggested that PDGFRβ+ pericytes contribute to scar formation (Arimura et al, 2012) and express fibroblast-associated markers (such as collagen IV, fibronectin and fibroblast surface proteins). Using a coll1a1 (collagen-1, α1) reporter mice to determine where scar-associated myofibroblasts generate extracellular matrix collagen type 1, Lin et al demonstrated that pericytes and perivascular muscle cells are a major source of myofibroblasts in a unilateral ureteral obstruction (UUO) kidney fibrosis model.…”
Section: Tissue Fibrosismentioning
confidence: 99%
“…26 One microgram of total RNA was reverse-transcribed in a total volume of 20 mL, and 0.5 mL of the product was used as a template. The mRNA copy numbers were standardized using 18 s ribosomal RNA (18 s rRNA).…”
Section: Reverse Transcription-pcr and Real-time Pcrmentioning
confidence: 99%